2010
DOI: 10.1002/adfm.201001008
|View full text |Cite
|
Sign up to set email alerts
|

Specific Colorimetric Detection of Proteins Using Bidentate Aptamer‐Conjugated Polydiacetylene (PDA) Liposomes

Abstract: The development of a bidentate aptamer-functionalized polydiacetylene (PDA) liposome sensor that is capable of specifi c colorimetric detection of proteins, directly in complex mixtures (e.g., serum), at sub-micromolar concentrations within 15 min, is reported. In comparison to sensors fabricated with a single aptamer reagent, the conjugation of bidentate aptamer pairs that recognize two distinct exosites of the target protein (thrombin) to the liposome results in signifi cant enhancements of the sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 54 publications
0
65
0
Order By: Relevance
“…6 We observed that in the absence of EpCAM, ACP probes are monodisperse and spherical in shape with an approximate diameter of ~364 nm (Fig. S4a and S4d † ).…”
mentioning
confidence: 84%
“…6 We observed that in the absence of EpCAM, ACP probes are monodisperse and spherical in shape with an approximate diameter of ~364 nm (Fig. S4a and S4d † ).…”
mentioning
confidence: 84%
“…All measurements were carried out at 25°C in a cell with an optical path length of 1 cm. To quantify the blue-to-red color transition of PDA vesicles interacting with DNA, the colorimetric response (CR) was calculated as follows: CR (%) ¼[(PB 0 À PB 1 )/PB 0 ] Â 100%, where PB¼A blue /(A blue þA red ); A is the absorbance of the blue (∼645 nm) or red (∼541 nm) component in the UV-visible absorption spectrum; PB 0 is the blue/red ratio of the control sample in the absence of DNA; and PB 1 is the value of the sample after the color change in the presence of DNA (Jung et al, 2010). To determine the limit of detection (LOD) of our sensor with clinical dsDNA samples, various concentrations of 605-bp amplicons were mixed with 9AA-conjugated PDA vesicles.…”
Section: Colorimetric and Spectrophotometric Detection Of Dnamentioning
confidence: 99%
“…Samples were incubated for 1 h and the relationship between dsDNA concentration and quantitative CR value was plotted to determine the LOD. Previous studies have suggested that a change in CR of 10% is readily discernible by the unaided human eye (Jung et al, 2010). Using this metric, we estimate the limit of visual detection of our sensor.…”
Section: Colorimetric and Spectrophotometric Detection Of Dnamentioning
confidence: 99%
See 2 more Smart Citations